Faktor-faktor Internal Penentu Profitabilitas Perbankan pada Bank Muamalat Indonesia - Diyah Ariyani; Maulida Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to find evidence of the effect of CAR, NPF, NOM and FDR on profitability. This type of research is quantitative research. The population in this study is the financial statements of Bank Muamalat Indonesia from 2015-2022. The sampling technique used uses saturated samples, where all members of the population are used as research samples. This study uses the strategy variables CAR (X1), NPF (X2), NOM (X3), FDR (X4), and ROA (Y). This study uses ECM analysis with the help of Eviews 12. The results show that X1 in the short term and long term has a positive and significant effect on Y, X2 in the short term has a negative and significant effect on Y while in the long term it has a negative and insignificant effect on Y, X3 has a positive and significant effect on Y, X4 has a positive and significant effect on Y.